2016
DOI: 10.1111/cas.12989
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA ROR promotes proliferation, migration and chemoresistance of nasopharyngeal carcinoma

Abstract: Nasopharyngeal carcinoma (NPC) is one of the most common malignancies of the head and neck. It arises from the nasopharynx epithelium and is associated with high morbidity and mortality. Long non‐coding RNA (lncRNA) have been reported to regulate gene interaction and play critical roles in carcinogenesis and progression. LncRNA‐ROR, a recently identified lncRNA, has been shown to be involved in initiation, progression and metastasis of several tumors, including hepatocellular carcinoma, breast cancer and gliom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
105
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 24 publications
2
105
0
Order By: Relevance
“…High expression of LincRNA-ROR is observed in multiple cancer types, including breast, bladder, and nasopharyngeal carcinoma [57][58][59]. Ectopic expression of LincRNA-ROR in cancer cells was associated with enhanced migration, invasion and EMT in vitro and metastasis in vivo.…”
Section: Lincrna-rormentioning
confidence: 99%
“…High expression of LincRNA-ROR is observed in multiple cancer types, including breast, bladder, and nasopharyngeal carcinoma [57][58][59]. Ectopic expression of LincRNA-ROR in cancer cells was associated with enhanced migration, invasion and EMT in vitro and metastasis in vivo.…”
Section: Lincrna-rormentioning
confidence: 99%
“…This study demonstrated that lncRNA CCAT1 affected the sensitivity of paclitaxel in NPC cells through miR-181a/CPEB2 associated signaling cascade [75]. LncRNA-regulator of reprogramming (ROR), a recently identified lncRNA, has been shown to be involved in initiation, progression and metastasis of several tumors including NPC [47, 76-78]. LncRNA-ROR, located at chromosome 18q21.31, was first discovered in induced pluripotent stem cells (iPSCs) and was directly regulated by stem cell (SC) markers SOX2, OCT4, NONOG, which were crucial for progression of various human malignancies including NPC [79].…”
Section: Oncogenic Lncrnasmentioning
confidence: 99%
“…LncRNA-ROR, located at chromosome 18q21.31, was first discovered in induced pluripotent stem cells (iPSCs) and was directly regulated by stem cell (SC) markers SOX2, OCT4, NONOG, which were crucial for progression of various human malignancies including NPC [79]. LncRNA-ROR was reported to be highly associated with the proliferation and metastasis of NPC [47]. Importantly, the enrichment of lncRNA-ROR played a key role in chemoresistance through mechanism by which lncRNA-ROR suppressed p53 signal pathway [47].…”
Section: Oncogenic Lncrnasmentioning
confidence: 99%
“…Li et al [51] found that LncRNA-ROR overexpression in human nasopharyngeal carcinoma and nasopharyngeal carcinoma cell lines and found that lncRNA-ROR expression levels were detected by RT-PCR The expression of lncRNA-ROR in nasopharyngeal carcinoma (CNE2, CNE1, 5-8F, 6-10B) was also higher than that in normal nasopharyngeal epithelium NP69 high. Study further demonstrated that lncRNA-ROR by regulating the cell cycle and promote the proliferation of nasopharyngeal carcinoma cells by affecting the epithelial mesenchymal transition and promote cell migration and invasion of nasopharyngeal carcinoma, the study discovers the lncRNA-ROR through the P53 pathway to produce chemotherapy resistance in nasopharyngeal carcinoma cells.…”
Section: Lncrna-rormentioning
confidence: 99%
“…It shows the characteristics lncRNA-ROR Tissue, cell Invasion, metastasis, chemotherapy-resistant Up-regulation [51] of paternally imprinted, selective expression of the maternal allele, the differentially methylated region is mainly affected by the upstream 4000 bp rich CpG island methylation regulation (DMR). H19 can regulate the growth and development of the embryo, but the expression of H19 is inhibited in the majority of tissues and organs after birth.…”
Section: H19mentioning
confidence: 99%